Structure-based drug design for envelope protein E2 uncovers a new class of bovine viral diarrhea inhibitors that block virus entry - Pascual, María José (2018)
Antiviral targeting of virus envelope proteins is an effective strategy for therapeutic intervention of viral infections. Here, we took a computer-guided approach with the aim of identifying new antivirals against the envelope protein E2 of bovine viral diarrhea virus (BVDV). BVDV is an enveloped virus with an RNA genome responsible for major economic losses of the cattle industry worldwide. Based on the crystal structure of the envelope protein E2, we defined a binding site at the interface of the two most distal domains from the virus membrane and pursued a hierarchical docking-based virtual screening search to identify small-molecule ligands of E2. Phenyl thiophene carboxamide derivative 12 (PTC12) emerged as a specific inhibitor of BVDV replication from in vitro antiviral activity screening of candidate molecules, displaying an IC50 of 0.30 μM against the reference NADL strain of the virus. Using reverse genetics we constructed a recombinant BVDV expressing GFP that served as a sensitive reporter for the study of the mechanism of action of antiviral compounds. Time of drug addition assays showed that PTC12 inhibited an early step of infection. The mechanism of action was further dissected to find that the compound specifically acted at the internalization step of virus entry. Interestingly, we demonstrated that similar to PTC12, the benzimidazole derivative 03 (BI03) selected in the virtual screen also inhibited internalization of BVDV. Furthermore, docking analysis of PTC12 and BI03 into the binding site revealed common interactions with amino acid residues in E2 suggesting that both compounds could share the same molecular target. In conclusion, starting from a targeted design strategy of antivirals against E2 we identified PTC12 as a potent inhibitor of BVDV entry. The compound can be valuable in the design of antiviral strategies in combination with already well-characterized polymerase inhibitors of BVDV.